Effectiveness of Simulating Magnetotransfer Therapy in Reducing the Severity of Depression in Post Stroke Patients - Lela Nurlela; Susanto; Hardianti; Satria Eureka Nurseskasatmata; Nur Syamsi Norma Lalla; M. Khalid Fredy Saputra (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Stroke is an acute neurovascular disorder that causes long-term limitations to daily living activities and death throughout the world, causing sufferers to experience motor and cognitive impairment. Until now, patients suffering from brain injuries require Transcranial Magnetic Stimulation with a method that non-invasively stimulates and studies the cerebral cortex which is large enough to produce the release of action potentials. Objective: The aim of the research is to determine the effect of providing transmagnetic stimulation therapy on improving post-stroke depression. Method: This research design uses a Nonequivalent control group design, where there are 2 groups, namely a control group and an intervention group, each group is measured 2 times, then the level of improvement in depression is assessed using the Hamilton depression rating scale score. Results: The results obtained for the control group were 0.302 > 0.05 and the significant value for the intervention group was 0.000 < 0.05. Conclusion: it can be concluded that there is a significant difference between the average post test score of the control group and the average post test score of the intervention group.